Molecular characterization of Brucella species detected from clinical samples of cattle and buffaloes - THORAT, VARSHA (The Indian Journal of Animal Sciences, 2022)
The present study was undertaken for molecular characterization of Brucella species of cattle and buffaloes. Clinical samples (1145) of unvaccinated cattle and buffaloes (200 blood samples, 710 sera, 190 vaginal swabs, 20 abomasal contents of foetus, 25 foetal tissues) and 146 blood samples of vaccinated animals were collected from dairy farms in and around Mumbai and Pune region. These samples were processed for isolation of Brucella organisms and further characterized by PCR and sequencing. A total of 26 (11.06%) Brucella isolates were recovered from 235 samples. Also, 5 isolates received from human cases were included in the study. BCSP 31 PCR showed an amplicon of 223 bp in all 31 isolates, 123 (61.5%) blood samples, 123 (64.73%) vaginal swabs and 27 (60%) aborted foetal material. IS711/AB and BM PCR showed an amplicon of 498 bp and 731 bp in 17 and 14 isolates, 42 (21%) and 38 (19%) blood samples, 43 (22.63%) and 34 (17.89%) vaginal swabs, while 7(15.55%) and 6 (13.33%) aborted foetal material, respectively. The phylogenetic analysis detected the ancestral origin of the organism. Rapid and correct diagnosis of brucellosis and vaccination is important to eradicate the disease. The molecular methods used in the present study speed up the diagnosis of the disease.